Treatment of infections caused by critically resistant Klebsiella pneumoniae strains: Current challenges and future prospectives. - Amira M. El-Ganiny (Zagazig Journal of Pharmaceutical Sciences)
Klebsiella is a Gram-negative bacterium that belongs to family Enterobacteriaceae. Klebsiella pneumoniae is the most pathogenic species of this genus that causes a number of nosocomial and community-acquired infections. Due to the misuse of antibiotics, K. pneumoniae acquires different genetic elements leading to the development of multidrug resistance (MDR) and extremely drug-resistant (XDR) strains. Among the emerged resistant strains, carbapenem-resistant K. pneumoniae (CRKP), extended-spectrum beta-lactamases (ESBL) producing K. pneumoniae, as well as MDR hypervirulent (Hv)-K. pneumoniae strains represent a global threat. These K. pneumoniae strains cause severe infections which lack effective therapy. CRKP is on the top of the priority pathogens list published by the world health organization (WHO) in 2024, for which the development of new therapeutic options is critical. This minireview discusses the evolution of the critically resistant K. pneumoniae strains and highlights the available treatment options for these strains. In addition, the novel therapeutic strategies that are still in research stages or under clinical trials will be reported herein.